CO2 uptake potential due to concrete carbonation: A case study - Edna Possan; William A. Thomaz; Gustavo A. Aleandri; Emerson F. Felix; Ana C.P. dos Santos (Case Studies in Construction Materials, 2017)
The cement manufacturing process accounts for about 5% CO2 (carbon dioxide) released into the atmosphere. However, during its life cycle, concrete may capture CO2 through carbonation, in order to, partially, offset the impact of its production. Thus, this paper aims at studying the CO2 uptake potential of the Itaipu Dam due to concrete carbonation of such material. So, 155 cores were extracted from the concrete dam in different points to measure carbonation depth. In order to evaluate its influence on carbonation, the measurement of internal moisture distribution in concrete was also carried out. The results have shown that carbonation takes part of the whole dam area, indicating CO2 uptake potential. Up to the present moment, 13,384 tons of CO2 have been absorbed by concrete carbonation of the Itaipu Dam.